Grain Boundary Diffusion with Simultaneous Chemical Interaction in Grain Boundary - Petelin, A.L.; Bokstein, B.S. (Металлофизика и новейшие технологии, 2013)
The new model is developed, taking into account the simultaneous grain boundary diffusion (within the Fisher—Gibbs approximation) and chemical interaction, which leads to the AB-type molecules’ formation in a binary system. The evaluation of ‘reaction’ effect on the rate of the whole process is made. Розглянуто нову модель, що враховує дифузію вздовж меж зерен (в рамках апроксимації Фішера—Ґіббса) одночасно з хімічною взаємодією, яка веде до утворення молекул типу АВ у бінарних системах. Зроблено оцінку впливу «реакції» на швидкість процесу в цілому. Рассмотрена новая модель, которая учитывает диффузию по границам зёрен (в рамках аппроксимации Фишера—Гиббса) одновременно с химическим взаимодействием, ведущим к образованию молекул типа АВ в бинарных системах. Сделана оценка влияния «реакции» на скорость процесса в целом.